2003
DOI: 10.1074/jbc.m209492200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Physical Interaction of Gli Proteins with SUFU Proteins

Abstract: The Hedgehog signaling pathway is involved in both development and cancer induction in a wide range of organisms. The end point of the Hedgehog signal-transduction cascade is the Gli/Ci, zinc-finger transcription factors. Proteins such as Fused, Suppressor of fused (SUFU), Costal-2, and protein kinase A are essential for regulation of Gli/Ci processing, activity, and localization. Coimmunoprecipitation and Far Western assays, coupled with truncation analysis and mutagenesis have been used to define the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(174 citation statements)
references
References 35 publications
(37 reference statements)
13
157
2
Order By: Relevance
“…4). SUFU-DsRed was observed predominantly in the cytoplasm and to a lesser degree in the nucleus when expressed alone, in agreement with previous reports (22,26). However, SUFU was largely (Ͼ80% of cells) localized to the nucleus in cells in which SUFU was co-expressed with Glis3 (Fig.…”
Section: The Region Of Glis3 Between Amino Acids 296 and 354 Is Highlsupporting
confidence: 81%
See 2 more Smart Citations
“…4). SUFU-DsRed was observed predominantly in the cytoplasm and to a lesser degree in the nucleus when expressed alone, in agreement with previous reports (22,26). However, SUFU was largely (Ͼ80% of cells) localized to the nucleus in cells in which SUFU was co-expressed with Glis3 (Fig.…”
Section: The Region Of Glis3 Between Amino Acids 296 and 354 Is Highlsupporting
confidence: 81%
“…A previous report showed that protein-protein interactions by SUFU involve recognition of an SYGH motif (22). Interestingly, Glis3 contains a similar motif, VYGH, located between amino acids 348 and 351 within the conserved region described above ( Fig.…”
Section: The Region Of Glis3 Between Amino Acids 296 and 354 Is Highlmentioning
confidence: 99%
See 1 more Smart Citation
“…Su(fu) tethers both the activator and repressor forms of Gli in the cytoplasm, resulting in downregulation of both activities 6,16 . Inhibition of Su(fu) by miR-214 in adaxial cells, which experience high amounts of Hedgehog signaling, allows maximal activation of Gli-mediated transcription (Fig.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Sufu (Suppressor of fused) acts as a central negative regulator of Hh signaling by sequestering the Gli transcription factors in an inactive complex (Kogerman et al , 1999; Dunaeva et al , 2003; Merchant et al , 2004; Humke et al , 2010). Sufu deletion in mice leads to the continuous activation of Hh signal and embryonic lethality at day 9.5 (Cooper et al , 2005; Svard et al , 2006), underscoring the essential role of Sufu for proper development.…”
Section: Introductionmentioning
confidence: 99%